Neotropical Mecoptera (Insecta): New generic synonymies, new combinations, key to families and genera, and checklist of species - Machado, Renato Jose Pires; Godoi, Fabio Siqueira P.; Rafael, José Albertino (Zootaxa, 2009)
Two Neotropical genera of Mecoptera (Thyridates Navás, 1908, Neobittacus Esben–Petersen, 1914 n. syn.) are synonymized under Bittacus Latreille, 1805. The following are new combinations: Bittacus aripuanaensis (Penny, 1977) n. comb., B. brunnipenis (Collucci & Amorim, 2000) n. comb., B. froehlichi (Collucci & Amorim, 2000) n. comb., B. latreillei (Collucci & Amorim, 2000) n. comb., B. novokschonovi (Petrulevičius, 2003) n. comb. and B. willmanni (Collucci & Amorim, 2001) n. comb.. A pictorial key to Neotropical families and genera and a checklist of Neotropical species are presented.